Emergency separation of a xipho-omphalopagus twin in a developing country - Shukla R; Mukhopadhyay B; Mandal K; Saha K; Roy D; Mukherjee P (Wolters Kluwer Medknow Publications, 2010)
Female conjoined twins (thoraco-omphalopagus) were delivered by emergency caesarean section in a private nursing home. On examination, one of the twins was dead and was threatening the survival of the surviving twin (twin A). An emergency separation was performed to salvage the surviving twin.